EDUCATION AS AN AGENT OF RESOCIALIZATION OF ELDERLY PEOPLE - Kalashnyk, Nataliia; Levchenko, Yana; Doronina, Olha; Kucherova, Olha; Luchenko, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Due to the aging of population there is a need for reevaluation of the importance and the necessity of elderly people’s participation in the life of society and as a result reevaluation of the methods of their adjustment. Modern “third aged people” want to continue living in the habitual rhythm of life, being the full participants of the society even after their retirement. The social portrait of a modern elderly differs significantly from the one 15-20 years ago. The level of medicine in the developed countries provides them with good state of health and therefore they can retain high level of social and emotional activity. Using several countries (Japan, Australia, Canada,) as an example the article aims to present different ways of inclusion of elderly people in socially useful activities in order to solve the problems of the modern society, in other words, to suggest how third aged people may be helpful. The article sums up that giving the opportunity of social and professional activity to the elderly people helps them to prevent social maladjustment and arising feeling of needlessness after the termination of active employment.